2020
DOI: 10.1155/2020/8305304
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Postpartum Depressive Symptoms in Community of Central Nepal

Abstract: Background. Pregnancy and postpartum are considered as high risk periods for the emergence of psychiatric disorder. Although postpartum depressive symptoms have been associated with tragic outcome, such as maternal suicide and infanticide, it is a neglected area of mental health care in developing countries. This study was conducted to find the prevalence and factors associated with postpartum depressive symptoms. Method. A community-based cross-sectional research design was carried out after selecting the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
6
1
Order By: Relevance
“…In relation to the prevalence of maternal depressive symptoms, it was found that 3.8% had moderate depressive symptoms and 2.2% had severe symptoms. These figures are lower than those reported in LAC countries such as Brazil ( Bozzini et al, 2021 ), Argentina ( Mathisen et al, 2013 ), India ( Neelakanthi et al, 2021 ), Nepal ( Dawadi et al, 2020 ), and Vietnam ( Van Vo et al, 2017 ), where higher figures of moderate and severe depressive symptoms were observed in mothers compared to the present study. Although the present study used the PHQ-9 which is a scale previously validated in the Peruvian population to measure depressive symptoms in the last 14 days prior to the survey ( Calderón et al, 2012 ), these differences could be attributed to the use of different scales to measure depressive symptoms in different time periods in mothers, where all the studies included in the comparison used the Edinburgh Postnatal Depression Scale (EPDS) that measures depressive symptoms in the 7 days prior to the survey, which could lead to higher prevalence of depressive symptoms in a short period of time.…”
Section: Discussioncontrasting
confidence: 93%
“…In relation to the prevalence of maternal depressive symptoms, it was found that 3.8% had moderate depressive symptoms and 2.2% had severe symptoms. These figures are lower than those reported in LAC countries such as Brazil ( Bozzini et al, 2021 ), Argentina ( Mathisen et al, 2013 ), India ( Neelakanthi et al, 2021 ), Nepal ( Dawadi et al, 2020 ), and Vietnam ( Van Vo et al, 2017 ), where higher figures of moderate and severe depressive symptoms were observed in mothers compared to the present study. Although the present study used the PHQ-9 which is a scale previously validated in the Peruvian population to measure depressive symptoms in the last 14 days prior to the survey ( Calderón et al, 2012 ), these differences could be attributed to the use of different scales to measure depressive symptoms in different time periods in mothers, where all the studies included in the comparison used the Edinburgh Postnatal Depression Scale (EPDS) that measures depressive symptoms in the 7 days prior to the survey, which could lead to higher prevalence of depressive symptoms in a short period of time.…”
Section: Discussioncontrasting
confidence: 93%
“…15 A hospital-based analytical cross-sectional study was conducted among 415 randomly selected postpartum mothers attending the child immunization clinic at Narayani hospital showed a significant association of postpartum depression with the family income, presence of husband during the pregnancy and whether the recent pregnancy was planned or unplanned which was somewhat similar to the associated factors of this study. 16…”
Section: Discussionmentioning
confidence: 99%
“…Initially, we expected that the associations of PCMC with depressive symptoms and mental well-being in urban areas would be different from those in rural areas. Previous studies in Nepal reported that 17.1–30.3% of mothers had depressive symptoms in urban areas, while 9.8% of women were distressed in rural areas [ 19 , 20 , 41 , 42 ]. The mean PCMC scores also varied depending on the settings.…”
Section: Discussionmentioning
confidence: 99%
“…PCMC is also necessary to prevent mothers’ mental problems and improve their well-being. Nowadays, postpartum depressive symptoms are gradually gaining attention in Nepal [ 19 , 20 ]. However, how the childbirth experiences at healthcare facilities, particularly with PCMC, are associated with women’s mental health after delivery in Nepal remains unknown.…”
Section: Introductionmentioning
confidence: 99%